Simulasi Pengaturan Waktu Delay pada Pelican Crossing di Jalan Dharmawangsa dalam untuk Meminimalkan Waktu Tunggu Kendaraan di Kampus B Universitas Airlangga - Vivian Angelina; Aprilia Margareta Andreas; Nathanel Wardana; Norbert Isa Yoga (Pusat riset dan Inovasi Nasional, 2025)
The objective of this study is to examine the simulation of delay time settings on the pelican crossing to minimize vehicle waiting time. The research was conducted through direct observation at two pelican crossing points behind UNAIR Campus B, specifically at the entrance gate side and the opposite side, to capture real usage conditions during peak student hours. This study employs a quantitative approach using the Discrete Event Simulation (DES) method to model and analyze the behavior of the pelican crossing system under various delay time and signal duration scenarios, with the aim of minimizing vehicle waiting time on Dharmawangsa Street,